2015
DOI: 10.1089/cbr.2014.1713
|View full text |Cite
|
Sign up to set email alerts
|

VIDA: A Voxel-Based Dosimetry Method for Targeted Radionuclide Therapy Using Geant4

Abstract: We have developed the Voxel-Based Internal Dosimetry Application (VIDA) to provide patient-specific dosimetry in targeted radionuclide therapy performing Monte Carlo simulations of radiation transport with the Geant4 toolkit. The code generates voxel-level dose rate maps using anatomical and physiological data taken from individual patients. Voxel level dose rate curves are then fit and integrated to yield a spatial map of radiation absorbed dose. In this article, we present validation studies using establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…32 The latter, based on Fortran, presents significant speed advantages over other Monte Carlo platforms in voxelized geometries. Others were developed ad hoc using opensource Monte Carlo collaborations, like VIDA 19 or RAY-DOSE, 33 that implement a patient-specific dosimetry Medical Physics, 47 (9), September 2020 calculation with Geant4. Recently, the platform RAPID has been introduced, 34 a patient-specific Geant4-based dose calculator for molecular radiotherapy, which calculates on the CT of the patient, with sources constructed from PET/SPECT images.…”
Section: Introductionmentioning
confidence: 99%
“…32 The latter, based on Fortran, presents significant speed advantages over other Monte Carlo platforms in voxelized geometries. Others were developed ad hoc using opensource Monte Carlo collaborations, like VIDA 19 or RAY-DOSE, 33 that implement a patient-specific dosimetry Medical Physics, 47 (9), September 2020 calculation with Geant4. Recently, the platform RAPID has been introduced, 34 a patient-specific Geant4-based dose calculator for molecular radiotherapy, which calculates on the CT of the patient, with sources constructed from PET/SPECT images.…”
Section: Introductionmentioning
confidence: 99%
“…Die [52,53]. In der phantombasierten Dosimetrie werden die Lage, Masse, Form und Absorptionseigenschaften der Organe basierend auf Populationsdaten (vor)definiert [54].…”
Section: Vorhersage Der Pharmakokinetik Während Der Therapieunclassified
“…Furthermore, the dose can also be expressed by [12] (5) from equation (5) it is observed that !Q = Y E " Q r ;…”
Section: Dose Approach By Means Of Stopping Power Functionmentioning
confidence: 99%
“…Numerically, it can be inferred through Monte Carlo (MC) simulations [4,5], and analytically it can be derived from S values tables [6,7] or by the Dose Point Kernels (DPK) convolution [8,9] taking into account data from media and radionuclides involved. When performing dosimetry at organ level, it is customary to introduce some approximations like assuming uniformity in the activity distribution within the source regions and/or homogeneous tissue distribution on treated patient region.…”
Section: Introductionmentioning
confidence: 99%